Pengaruh Substitusi Bubur Kulit Pisang Ambon Lumut (Musa accuminata Colla) pada Terigu terhadap Karakteristik Donat - Nurhasanah, Ai; Ningrumsari, Ida; Herlinawati, Lina (Ma'soem University, 2024)
Donuts are a food made from the main ingredients of flour, yeast, sugar and water and then decorated using various toppings so that this food is a favorite of almost all people. Ambon lumut banana fruit is a fruit that is often used as the main ingredient or filling material by some food entrepreneurs or communities in Indonesia, so that Ambon lumut banana peels accumulate into waste which pollutes the quality of the environment if handled improperly. One good form of processing is to utilize Ambon moss banana peels into products with economic value. Ambon moss banana peels are made into banana peel pulp as a substitute for wheat flour in the process of making donuts. The aim of the research was to produce the best substitute for Ambon Lumut banana peel porridge for wheat in terms of donut organoleptics, water content, carbohydrates and crude fiber. The method used was a Randomized Block Design (RAK), each substitution was repeated five times. Substitution of Ambon banana peel pulp for flour starts from 5%, 10%, 15% and 20%. The best substitution was treatment P5 (20%) based on Duncan's multiple wine test and scoring test with average values ??of water content (24.05%), carbohydrate content (23.36%), and crude fiber (8.16%). Organoleptic test for color 2.68 (usual), taste 4.16 (like), aroma 4.28% (like) and tenderness 4.44 (like).